Rate and risk factors for inpatient falls following single-level posterior lumbar fusion: A national registry study - Michael J. Gouzoulis, BS; Sahir S. Jabbouri, MD; Anthony E. Seddio, BS; Jay Moran, MD; Wesley Day, BS; Philip P. Ratnasamy, BS; Jonathan N. Grauer, MD (North American Spine Society Journal)
Background: Posterior lumbar fusion (PLF) is frequently considered for various spinal pathologies. While many outcome metrics have been assessed, to our knowledge, there has yet to be literature specifically investigating inpatient falls (IPFs) and its risk factors. Methods: Adult patients who underwent single-level PLF were abstracted from the 2010–Q1 2022 M161Ortho PearlDiver Database. Patients who had an IPF were determined based on administrative coding. Various patient variables were extracted and variables independently associated with IPFs were assessed with multivariate logistic regression. Incidence of secondary injuries and cost incurred related to the IPF were determined. Results: Of the 342,890 patients who underwent PLF, IPF was identified for 4,379 (1.4%). Independent predictors of an IPF in decreasing odds ratio (OR) order were those with: active psychosis (OR=3.35), active delirium (OR=2.83), history of falling (OR=2.47), commercial insurance (OR=1.59 relative to Medicare), Medicaid insurance (OR=1.47 relative to Medicare), dementia (OR=1.17), older age (OR=1.12 per decade), alcohol use disorder (O=1.11), higher comorbidity (OR=1.08 per Elixhauser comorbidity index point) (p<.05 for each).Of patients with IPF, 44 (1.0%) sustained a head injury, and 42 (1.0%) sustained a fracture. On average, those with IPF incurred greater inpatient costs compared to patients who did not ($36,865 vs. $33,921, p<.001). Conclusion: In this national sample of patients who underwent single-level PLF, postoperative IPFs were identified for 1.4% and were associated with defined patient variables. These findings have potential patient outcome, financial, and medicolegal implications and should help guide refinement of fall prevention programs.